PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI SMP NEGERI 10 PALEMBANG - Zainal Berlian; Kurratul Aini; Siti Nur Hikmah (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
Cooperative learning model make a match is a learning model that motivates all students to be active and provide an opportunity for students to think, free expression of thought according tothe results they get. The learning result is the ability gained after the child through learningactivities. Children who succeed in learning is successfully achieving the goals of learning orinstructional objectives. This study was conducted on August 22, 2016. The objective of thisresearch is to know the influence of model make a match of the student learning outcomes ofSMP Negeri 10 Palembang. This research method used of true experimental design with aquantitative approach research with posttest only control design. The data on the calculationdifference average posttest both groups earned value t-test as much as 3,09 while t-table valuewith significant level 5 % with degrees of freedom (dk) 58 is equal to 2.00, it can be said thatt-test > t-table means that the alternative hypothesis accepted and the null hypothesis rejected.This shows that there were a significant the implementation of make a match of the studentlearning outcomes of SMP Negeri 10 Palembang.